Paradigma Hukum Kedudukan Kepolisian Negara Republik Indonesia Dalam Pengamanan Aksi Unjuk Rasa - Arnapi; Karnaji; Abidin, Izzah Khalif Raihan; Arsyada, Rofadan Mina (Media Iuris, 2024)
AbstractThe law will continue to develop to achieve justice. In social life, the Indonesian National Police is essential in ensuring security and order, including demonstrations by certain groups of people. Indonesia, as a democratic country, absolutely guarantees the existence of public opinion, namely freedom of speech, freedom of the press, intellectual freedom, and freedom of religion, as stated in Article 28E paragraph (3) of the 1945 Constitution of the Republic of Indonesia and detailed in other laws and regulations. Departing from the issue of violence in demonstrations, we will discuss the legal urgency of granting constitutional rights to demonstrations, the status and criminal responsibility of the Indonesian National Police in security and state order. The inconsistency in the recognition of constitutional rights at demonstrations can be seen in the criminal sanctions for the Indonesian National Police who commit acts that violate the law that have not been applied strictly and proportionately.Keywords: Rally; Constitutional Rights; Human Rights; Criminal Liability; The Indonesian National Police. AbstrakHukum akan terus berkembang untuk mencapai suatu keadilan. Dalam kehidupan sosial bermasyarakat, Kepolisian Republik Indonesia memegang peranan penting untuk menjamin keamanan dan ketertiban salah satunya aksi unjuk rasa yang dilakukan oleh sekelompok orang tertentu. Indonesia sebagai negara demokrasi secara absolut menjamin eksistensi pendapat umum yakni kebebasan berbicara, kebebasan pers, kebebasan intelektual, dan kebebasan beragama sebagaimana Pasal 28E ayat (3) Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 dan diperinci dalam peraturan perundang-undangan lainnya. Berangkat pada isu kekerasan dalam aksi unjuk rasa, akan dibahas urgensi hukum pemberian hak konstitusi pada unjuk rasa, kedudukan dan pertanggungjawaban pidana Kepolisian Republik Indonesia dalam keamanan dan ketertiban negara. Inkonsistensi pengakuan hak konstitusi pada unjuk rasa nampak pada sanksi pidana bagi POLRI yang melakukan perbuatan melanggar hukum yang belum diterapkan secara tegas dan proporsional.Kata Kunci: Unjuk Rasa; Hak Konstitusi; Hak Asasi Manusia; Pertanggungjawaban Pidana; Kepolisian Negara Republik Indonesia.